Sarcomatoid carcinoma of colon: extremely poor prognosis - Choi, Yoon Young (The Korean Surgical Society, 2011)
Colonic sarcomatoid carcinomas are known to be extremely rare tumors, with only 22 cases reported either as sarcomatoid carcinomas or carcinosarcomas in the literature. The known characteristics are rapid growth, a high recurrence rate, and an extremely poor prognosis. Herein we report a case of a patient who had a sarcomatoid carcinoma of the sigmoid colon and died only 22 days after surgery due to rapid tumor growth.